Respuesta :
Answer:
[tex]f(g(x))=x[/tex]
Step-by-step explanation:
Given a certain function [tex]f(x)[/tex], and then its inverse function [tex]f^{-1}(x)[/tex], the following expression is valid:
[tex](f\cdot f^{-1})(x)=x[/tex]
where the expression
[tex](f\cdot f^{-1})(x)=f(f^{-1}(x))[/tex]
indicates the composite function.
In this problem, we have:
[tex]f(x)=5x-25[/tex]
And then, its inverse function is
[tex]g(x)=\frac{1}{5}x+5[/tex]
To verify that g(x) is the inverse of f(x), the following expression must be true:
[tex]f(g(x))=x[/tex]
Substituting the expression of g(x) into f(x), we find that:
[tex]f(g(x))=5g(x)-25=5(\frac{1}{5}x+5)-25=x+25-25=x[/tex]
So, g(x) is the inverse of f(x).